EVERY NOTE COUNTS, A CLINICAL AUDIT ON MEDICAL RECORD QUALITY IN A MULTISPECIALTY TERTIARY HOSPITAL IN PAKISTAN (The Research of Medical Science Review, 2025)
Background: Effective documentation is vital for quality clinical care, enabling proper treatment planning and continuity across providers. This audit assessed inpatient records in a multi-specialty hospital for compliance with established documentation standards.Aims and ObjectivesTo assess medical notes quality across departments at Gulab Devi Teaching Hospital and suggest solutions to enhance records and address deficiencies.Method(s)A retrospective audit was carried out at Gulab Devi Teaching Hospital from July 1st to December 31st, 2024. Out of 10,000 patients admitted during this period, 1,000 case notes were randomly selected for review. The clinical documentation was evaluated based on structured parameters set by the Punjab Healthcare Commission (PHC) and analyzed using MATLAB.Results This audit shows that targeted interventions improved documentation, raising compliance from 88.1% to 98.9%, enhancing safety, continuity, and accountability.ConclusionThe audit reveals initial inadequate documentation practices in patient charts, posing significant risks for care and retrospective analyses. Subsequent orientation sessions significantly improved records, underscoring the importance of structured training to meet established documentation standards.